CORRECTION OF ENDOTHELIAL DYSFUNCTION IN PATIENTS WITH CHRONIC COR PULMONALE BY ANGIOTENSIN II RECEPTORS ANTAGONISTS - V. S. Zadionchenko; N. B. Holodkova; O. I. Nesterenko; I. V. Pogonchenkova; A. M. Shchikota; Y. V. Ignatova; I. Y. Malyshev; E. B. Manukhina; S. V. Kruglov; D. A. Pokidyshev; O. A. Zemnina (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To evaluate intensity of endothelial dysfunction, processes of apoptosis, state of central and peripheral hemodynamics and to evaluate how these characteristics are influenced by angiotensin II receptors antagonists (ARA II) – candesartan (Atacand) and losartan (Cosaar) in patients with chronic cor pulmonale (CCP) at different stages of disease. Material and methods. 100 patients with chronic obstructive pulmonary disease (COPD), complicated by CCP were included into the study. Caspase activity as apoptosis induction marker, von Willebrand factor, production of nitric oxide in blood plasma and condensate of breathing out air were assessed. 70 patients received ARA II (50 patients – candesartan 4-8 mg daily, 20 patients – losartan 50-100 mg daily), 30 patients received neither ARA II nor angiotensin converting enzyme inhibitors (ACEI). Results. Significant increase in intensity of endothelial dysfunction and activation of apoptosis processes were registered according to growth of CCP severity. After 6 months of therapy von Willebrand factor decreased by 25,2% and 27,7% in candesartan and losartan groups respectively (p<0.01 for both groups). In the control group only 13.2% of von Willebrand factor reduction was seen. Conclusion. ARA II added to common therapy of COPD complicated by CCP improves functional state of endothelium restricting hyperproduction of nitric oxide and its toxic effects and slowing down apoptotic cell death.